Spatial analysis of the phenomenon of child labor in the city of Abu-Al khaseeb and its social impacts - Khudhair Salman AL Ali, Assist . Prof. Dr. Mohammed; Mustafa Mhawes, Assist. Prof. Dr. Ali; Ali Ghani Al-farhan, Researcher: Fatima (Basra studies journal, 2025)
Child labor is a widespread phenomenon in Basra province in general, and in Abu Al-Khaseeb District in particular, with a total of 284 children, distributed spatially across all neighborhoods in varying numbers. Social, economic, and educational factors combined to contribute to the spread of this phenomenon. Educational factors were the highest contributors to the spread of child labor, accounting for 42% of the total. Social factors came second, accounting for 30.4%, while economic factors came in last, accounting for 27.6%. The gender distribution of child labor was 61.2% for males, while females accounted for 38.8%. This phenomenon resulted in a number of consequences, the most important of which were deprivation of education, accounting for 43.5%, followed by physical violence, 23.5%, verbal violence, 17.5%, and underage marriage, accounting for 14.5%. Finally, the study concluded with a set of proposals to address and reduce this phenomenon.